2016
DOI: 10.1007/s11262-016-1312-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the in vitro replication and genomic variability of Argentinean field isolates of bovine herpesvirus type 4 (BoHV-4)

Abstract: Bovine herpesvirus 4 (BoHV-4) is a gammaherpesvirus, belonging to the Rhadinovirus genus, which is increasingly associated with various problems of the reproductive tract of cattle. In Argentina, analysis of BoHV-4 strains isolated from cervico-vaginal mucus of aborted cows revealed a high genetic divergence among strains, which could be classified in three different groups: Genotype 1 comprises Movar-like strains (European prototype), Genotype 2 includes DN599-like strains (American prototype) and Genotype 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
5
9
0
Order By: Relevance
“…coincidently, a significant variation in the kinetics of replication of different BoHV4 local isolates has been previously reported by our research group [35].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…coincidently, a significant variation in the kinetics of replication of different BoHV4 local isolates has been previously reported by our research group [35].…”
Section: Discussionsupporting
confidence: 81%
“…highlights the significance of studying the role of this virus. Furthermore, although the genomic characterization of these strains is currently being expanded, in previous studies, synonymous and non-synonymous substitutions have been observed in the gB, gH and Tk genes of the strains analyzed in this work [26,35].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Notably, virus genomic differences can potentially lead to different pathogenic potential. This was recently demonstrated in vitro when replication kinetics and virus titers of different BoHV-4 strains were compared (46). Most of the divergences between BoHV-4 genomes were in the Bo genes and in the repeat regions (Figure 2).…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, the findings of this study provide an initial step to understand the biology of the Argentinean isolates of BoHV-4. The high variability among strains isolated in Argentina (Verna et al 2012(Verna et al , 2016 highlights the significance of research on the role of this virus as an infectious agent capable of causing reproductive disease in cattle. This is the first report in Argentina on histopathological findings and tissue distribution of BoHV-4 in its natural host after an experimental infection…”
Section: Discussionmentioning
confidence: 99%